Analysis of Mechanical Properties and Mechanical Anisotropy in Canine Bone Tissues of Various Ages. (20th June 2019) - Luo, Changqi; Liao, Junyi; Zhu, Zhenglin; Wang, Xiaoyu; Lin, Xiao; Huang, Wei
Abstract : The effect of age on mechanical behavior and microstructure anisotropy of bone is often ignored by researchers engaged in the study of biomechanics. The objective of our study was to determine the variations in mechanical properties of canine femoral cortical bone with age and the mechanical anisotropy between the longitudinal and transverse directions. Twelve beagles divided into three age groups (6, 12, and 36 months) were sacrificed and all femurs were extracted. The longitudinal and transverse samples of cortical bone were harvested from three regions of diaphysis (proximal, central, and distal). A nanoindentation technique was used for simultaneously measuring force and displacement of a diamond tip pressed 2000nm into the hydrated bone tissue. An elastic modulus was calculated from the unloading curve with an assumed Poisson ratio of 0.3, while hardness was defined as the maximal force divided by the corresponding contact area. The mechanical properties of cortical bone were determined from 852 indents on two orthogonal cross-sectional surfaces. Mean elastic modulus ranged from 7.56±0.32 GPa up to 21.56±2.35 GPa, while mean hardness ranged from 0.28±0.057 GPa up to 0.84±0.072 GPa. Mechanical properties of canine femoral cortical bone tended to increase with age, but the magnitudes of these increase for each region might be different. The longitudinal mechanical properties were significantly higher than that of transverse direction ( P <0.01). A significant anisotropy was found in the mechanical properties while there was no significant correlation between the two orthogonal directions in each age group ( r 2 <0.3). Beyond that, the longitudinal mechanical properties of the distal region in each age group were lower than the proximal and central regions. Hence, mechanical properties in nanostructure of bone tissue must differ mainly among age, sample direction, anatomical sites, and individuals. These results may help a number of researchers develop more accurate constitutive micromechanics models of bone tissue in future studies.